Clinical and Procedural Predictors of Outcomes From the Endovascular Treatment of Posterior Circulation Strokes. Issue 3 (March 2016) - Mokin, Maxim; Sonig, Ashish; Sivakanthan, Sananthan; Ren, Zeguang; Elijovich, Lucas; Arthur, Adam; Goyal, Nitin; Kan, Peter; Duckworth, Edward; Veznedaroglu, Erol; Binning, Mandy J.; Liebman, Kenneth M.; et al.
Abstract : Background and Purpose—: Patients with posterior circulation strokes have been excluded from recent randomized endovascular stroke trials. We reviewed the recent multicenter experience with endovascular treatment of posterior circulation strokes to identify the clinical, radiographic, and procedural predictors of successful recanalization and good neurological outcomes. Methods—: We performed a multicenter retrospective analysis of consecutive patients with posterior circulation strokes, who underwent thrombectomy with stent retrievers or primary aspiration thrombectomy (including A Direct Aspiration First Pass Technique [ADAPT] approach). We correlated clinical and radiographic outcomes with demographic, clinical, and technical characteristics. Results—: A total of 100 patients were included in the final analysis (mean age, 63.5±14.2 years; mean admission National Institutes of Health Stroke Scale score, 19.2±8.2). Favorable clinical outcome at 3 months (modified Rankin Scale score ⩽2) was achieved in 35% of patients. Successful recanalization and shorter time from stroke onset to the start of the procedure were significant predictors of favorable clinical outcome at 90 days. Stent retriever and aspiration thrombectomy as primary treatment approaches showed comparable procedural and clinical outcomes. None of the baseline advanced imaging modalities (magnetic resonance imaging, computed tomographic perfusion, or computed tomography angiography assessment of collaterals) showed superiority in selecting patients for thrombectomy. Conclusions—: Time to the start of the procedure is an important predictor of clinical success after thrombectomy in patients with posterior circulation strokes. Both stent retriever and aspiration thrombectomy as primary treatment approaches are effective in achieving successful recanalization. Abstract : Supplemental Digital Content is available in the text.